OPTIMALISASI KEMAMPUAN MEMBACA PEMAHAMAN MELALUI PENINGKATAN PENGUASAAN STRUKTUR KALIMAT - Supriyono Supriyono (Khazanah Pendidikan, 2014)
The ability of reading comprehension is an ability, skill, and dexterity to empower the reader in cognitive function/ mental to understanding the emblem/ symbol written language such as words, phrases, sentences contained in the passage, either expressly (literal comprehension) or implied (comprehension interpretive, critical, creative) appropriately. Many possible factors that affect the ability to read one's understanding , such is its mastery of sentence structure. In other words, an increase in the ability of reading comprehension can be done through increasing mastery of sentence structure. In this case the control structure of the sentence is the person's level of mastery of the rules, the use of the term or phrase analysis contained in the passage, either on the form of the sentence , the meaning of the phrase , and sentence patterns. Through mastery strktur adequate sentence readers have the potential to quickly and accurately understand the emblem/ symbol written language contained in the passage either expressed or implied, as he has mastered the rules, the use of the term or phrase analysis contained in the passage , both regarding form of the sentence, the meaning of the phrase, and sentence patterns . Keywords : reading comprehension, sentence structure